Efisiensi Anggaran Melalui Penguatan Collaborative Network dalam Pelayanan Sosial: Studi Kasus Dinas Sosial Kota Surabaya dan Mitra Sektoral - Rohmatul Izah; Aditya Jaya Pratama; Dany Risky Eka Putra; Revienda Anita Fitrie (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This research aims to analyze strategies for budget efficiency by strengthening collaborative governance in delivering social services by the Social Service Office of Surabaya City. A qualitative approach was used through a study of planning documents and local media reports from 2021 to 2024. Content analysis was applied to identify partnership patterns among government institutions, social organizations, communities, and businesses involved in the implementation of social programs. The findings reveal that such collaborations significantly reduce the fiscal burden on the government, expand service outreach for vulnerable groups, and reinforce the sustainability of social programs. The established partnerships also accelerate aid distribution, improve coordination, and encourage innovation through community-based participation amid regional fiscal constraints.